2016
DOI: 10.6118/jmm.2016.22.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Age at Natural Menopause and Related Factors in Isfahan, Iran

Abstract: ObjectiveThis study was aimed to evaluate the age at natural menopause and related factors among women in a population based study in 2015 in Isfahan, Islamic Republic of Iran.MethodsIn this cross-sectional study 960 menopausal women were selected by cluster sampling. Demographic, socioeconomic, lifestyle behavior and reproductive history aspects were collected using a structured questionnaire. Woman and her husband's educational level and occupation with family income were the variables to construct socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
7
21
2
2
Order By: Relevance
“…Results of our study showed that the mean age of menopause in total population was 47.9 ± 5.7 and the mean age in natural and induced menopause was 49.2 ± 4.7 and 43.2 ± 6.4, respectively. Although the overall mean of menopause in our study is relatively similar to other province in Iran [11,12,[17][18][19], the mean age of natural menopause in Tabari cohort population is greater than other provinces except Hamedan (49.6 ± 4.0) [20]. Comparing to other countries, age of menopause in our study is less than Western world [6,21], but it is higher than Punjabi women (47.9 ± 3.2) [22].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Results of our study showed that the mean age of menopause in total population was 47.9 ± 5.7 and the mean age in natural and induced menopause was 49.2 ± 4.7 and 43.2 ± 6.4, respectively. Although the overall mean of menopause in our study is relatively similar to other province in Iran [11,12,[17][18][19], the mean age of natural menopause in Tabari cohort population is greater than other provinces except Hamedan (49.6 ± 4.0) [20]. Comparing to other countries, age of menopause in our study is less than Western world [6,21], but it is higher than Punjabi women (47.9 ± 3.2) [22].…”
Section: Discussionsupporting
confidence: 56%
“…Association between marital status and menopausal age was inconsistent in previous studies [19,20]. In our study the number of single participants was very low and therefore we could not compare them with married participants.…”
Section: Discussionmentioning
confidence: 68%
“…Age at menopause in our studied sample is similar to previous estimates reported for other Iranian populations .In a cross-sectional study on 960 menopausal women in 2015 in Isfahan mean and median of natural menopause age were 48.66 and 48 years, respectively (22). In the present study, the mean age at permanent cessation of menstrual periods has significantly been increased and reached by 48 years in 2016.…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies, especially those that hypothesized the influence of ovulation or follicle attrition, have shown somewhat controversial results with respect to the timing of natural menopause. our results are consistent with previous reports with regard to the influence of age at menarche [8,38], maternal age at menopause [19], age at marriage [39], and parity [40,41] on menopausal age. moreover, other analyses have reported that parity was not a prediction factor per se, but that age at last delivery was directly associated with menopausal age [42].…”
Section: Factors Affecting Menopausal Agesupporting
confidence: 93%